2017
DOI: 10.3390/rs9020110
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Comparison of Albedo Products for Glacier Surfaces Derived from Airborne and Satellite (Sentinel-2 and Landsat 8) Optical Data

Abstract: Surface albedo partitions the amount of energy received by glacier surfaces from shortwave fluxes and modulates the energy available for melt processes. The ice-albedo feedback, influenced by the contamination of bare-ice surfaces with light-absorbing impurities, plays a major role in the melting of mountain glaciers in a warming climate. However, little is known about the spatial and temporal distribution and variability of bare-ice glacier surface albedo under changing conditions. In this study, we focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 51 publications
4
97
0
1
Order By: Relevance
“…In agreement with previous satellite investigations on Alpine glaciers, low α VIS values are estimated in the Morteratsch ablation zone (Brun et al, 2015;Dumont et al, 2011;Fugazza et al, 2016;Klok et al, 2004;Naegeli et al, 2015Naegeli et al, , 2017. This decrease in albedo can be explained by both an increase in LAI content and/or variations of the snow and ice grain properties.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with previous satellite investigations on Alpine glaciers, low α VIS values are estimated in the Morteratsch ablation zone (Brun et al, 2015;Dumont et al, 2011;Fugazza et al, 2016;Klok et al, 2004;Naegeli et al, 2015Naegeli et al, , 2017. This decrease in albedo can be explained by both an increase in LAI content and/or variations of the snow and ice grain properties.…”
Section: Discussionsupporting
confidence: 90%
“…In general, in the entire visible spectrum, the reflection is very high: about 90% for snow and 65% for ice of glaciers. In contrast, in the shortwave infrared spectral reflection can be even lower than 10% [32].…”
Section: Detection Accuracy Of the Marginal Zone Of Glaciers-landsat mentioning
confidence: 98%
“…For such selected pixels, local statistics were calculated in a moving window with a size of 2 × 2 pixels. Based on the knowledge of the spectral reflection characteristics of ice [32], it was assumed that a difference of less than 0.1 between the panNDSI index values will not allow for a detailed distinction of the ice-ground boundary ( Figure 3F). As the local variation increases for pixels arranged along the ice border, the higher the possibility of automatic or semiautomatic classification.…”
Section: Detection Accuracy Of the Marginal Zone Of Glaciers-landsat mentioning
confidence: 99%
“…Several studies have estimated BRDFs and HCRFs of snow and sea ice surfaces (e.g. Hudson et al, 2006;Marks et al, 2015;Arnold et al, 2002), but equivalent measurements are scarce for glacier ice in various states of melt and impurity loading, although Naegeli et al (2015) measured HCRF for various surface types on an alpine glacier, and Gruell and de Ruyter de Wildt (1999) measured anisotropic reflection from melting glaciers in two Landsat Thematic Mapper bands. Naegeli et al (2017) recently showed that ice surfaces with higher impurity loads scatter more anisotropically, possibly due to locally enhanced melt.…”
Section: Characterising Abiotic Impuritiesmentioning
confidence: 99%
“…We have recently undertaken field work for this purpose and will publish the outcomes in a future paper. There is uncertainty in the biological literature concerning the impact of cell size on the optical properties of algae arising from the spatial distribution of pigments within cells (Haardt and Maske, 1987), variable intracellular architecture (Haardt and Maske, 1987), packaging effects (Morel and Bricaud, 1981) and non-linear relationships between cell growth and Figure 4. A constant biomass (0.5 mg algae /g ice , pigment mass fractions (% total cell dry mass) is 1.5 % chlorophyll a, 5 % primary and secondary carotenoids, 15 ”m cell radius) distributed vertically in layers of ice (1500 ”m grain radius) of varying thickness (1, 2, 3, 4, 5, 10 mm).…”
Section: Characterising the Optical Properties Of Individual Cellsmentioning
confidence: 99%